CD1b presents self and Borrelia burgdorferi diacylglycerols to human T cells. Issue 5 (20th March 2019) - Reinink, Peter; Souter, Michael N. T.; Cheng, Tan‐Yun; van Gorkom, Tamara; Lenz, Stefanie; Kubler‐Kielb, Joanna; Strle, Klemen; Kremer, Kristin; Thijsen, Steven F.T.; Steere, Allen C.; Godfrey, Dale I.; Pellicci, Daniel G.; et al.
Abstract: Lyme disease is a common multisystem disease caused by infection with a tick‐transmitted spirochete, Borrelia burgdorferi and related Borrelia species. The monoglycosylated diacylglycerol known as B. burgdorferi glycolipid II (BbGL‐II) is a major target of antibodies in sera from infected individuals. Here, we show that CD1b presents BbGL‐II to human T cells and that the TCR mediates the recognition. However, we did not detect increased frequency of CD1b‐BbGL‐II binding T cells in the peripheral blood of Lyme disease patients compared to controls. Unexpectedly, mapping the T cell specificity for BbGL‐II‐like molecules using tetramers and activation assays revealed a concomitant response to CD1b‐expressing APCs in absence of BbGL‐II. Further, among all major classes of self‐lipid tested, BbGL‐II responsive TCRs show strong cross‐reactivity to diacylglycerol, a self‐lipid antigen with structural similarities to BbGL‐II. Extending prior work on MHC and CD1b, CD1c, and CD1d proteins, this study provides evidence for cross‐reactive CD1b‐restricted T cell responses to bacterial and self‐antigens, and identifies chemically defined targets for future discovery of self and foreign antigen cross‐reactive T cells. Abstract : Borrelia burgdorferi causes Lyme disease. Here, we show that the human antigen presenting molecule CD1b presents a major glycolipid from B. burgdorferi to human T cells. These T cells cross‐react with the mammalian self‐lipid diacylglycerol.